The methodology of diagnostic competence formation of future physical training teachers - Gats G.O (Kharkov National Pedagogical University, 2010)
A content component of competence formation in the field of pedagogical diagnosis includes following interconnected components: 1) complex knowledge, which future specialist has to possess; 2) a system of practical abilities and skills that are fundamental for the diagnostic activity of a specialist; 3) experience in the field of diagnostic activity. Students' competence formation in the field of pedagogical diagnosis is possible in the framework of the higher education system. The indicators of dynamic self-evaluation are: the level of formation of the basic diagnostic knowledge and skills; the level of its application and awareness; the ability of future specialists to conduct diagnostic measures.